SMEs “growing smart” - Erjavec, Eva (Economic and business review, 2023)
Like large companies, small and medium-sized companies (SMEs) are turning to new digital technologies and knowledge-based capital to bolster their productivity and growth. However, data show that smaller companies lag significantly in implementing new Industry 4.0 technologies and in the intensity of their use. Lack of skills and human capital is often cited as one of the biggest barriers. This paper examines the benefits of digital technologies, intangible capital, and in particular the role of complementary investments in new technologies and intangible capital to maximize the impact on productivity growth. The analysis draws on extensive firm-level datasets combining business and employee registry data and the harmonized EU ICT usage survey for the period 2007-2020 in Slovenia. While SMEs lag behind large companies in the use of ICT on average, the use of ICT and other new technologies significantly increases the productivity of companies in the SME sector, especially when combined with the intangible investments that enhance the contribution of new technologies. Several conclusions emerge from the results, in particular the need to grow and invest intelligently, that is, to invest in intangible assets and new technologies simultaneously, even in SMEs.
Keywords: digitalizacija; digitalization; majhna in srednja podjetja; productivity; produktivnost; SMEs